Development of a Japanese Version of the Parenting Sense of Competence Scale, and Examining the Structure of Japanese Mothers’ Parenting Self-Efficacy - Tomomi Tanigo; Masayuki Endo; Kazutomo Ohashi (Children)
Objective: Parenting self-efficacy (PSE) is an important factor in children’s development. Mothers’ PSE tends to be the lowest 1 month postpartum. A common measure of PSE is the Parenting Sense of Competence (PSOC) scale. However, no existing scale measures the PSE of Japanese mothers with newborns. Therefore, this study developed a Japanese version of the PSOC scale for mothers 1 month postpartum (Study 1) and investigated the structure of their PSE (Study 2). Methods: In Study 1, data were collected from mothers 1 month postpartum from April to October 2017, and an exploratory factor analysis was performed on their PSOC scores. In Study 2, data were collected from mothers 1 month postpartum from January to September 2022. A confirmatory factor analysis was conducted of the Japanese PSOC scale developed in Study 1 to investigate the structure of the participants’ PSE 1 month postpartum. Results: In Study 1, a 2-factor (Efficacy and Satisfaction) 12-item Japanese PSOC scale was obtained after deleting four items because of low factor loadings. In Study 2, the model showed an acceptable fit. The Japanese PSOC (12 items) had a moderate positive correlation with Rosenberg’s Self-Esteem Scale and the Maternal Attachment Inventory and a moderate negative correlation with the Edinburgh Postpartum Depression Scale. Furthermore, mothers whose children had siblings (versus no siblings) and mothers with three children (versus two children) had significantly higher PSOC scores. Conclusions: We developed a reliable and valid Japanese version of the PSOC for mothers 1 month postpartum and revealed the structure of their PSE.